A4.5 Procollagen type 1 amino-terminal propeptide is negatively associated with bone stiffness in subpopulations of patients submitted to hip replacement surgery. (31st January 2014) - Gonçalves, MJ; Sepriano, A; Rodrigues, A; Lopes, A; Caetano-Lopes, J; Fonseca, JE; Canhão, H
Abstract : Background and Objectives: Osteoporosis (OP) is a frequent disorder of bone metabolism. In OP, cortical bone changes lead to bone loss and deterioration of the microarchitecture increasing risk of fragility fractures of the hip. Bone turnover markers (BTM) reflect bone remodelling. Their role in daily clinical practice is still undefined. In a recent epidemiologic study, a relation between P1NP and hip fractures was found, suggesting both low and high levels of P1NP confer increased risk of osteoporotic fractures. We aim to analyse the relation between BTM and biomechanical features of the bone, in patients with stabilised osteoporosis and in patient with severe osteoarthritis. Materials and Methods: We analysed patients submitted to hip replacement surgery in the context of severe OA or hip fragility fracture. The patients were asked for clinical data, blood samples and to perform dual x-ray absorptiometry. Blood biomechanical studies were performed and a bone cylinder was drilled from their femoral epiphyses. Stiffness, strength and toughness were assessed by young's modulus, yield stress and energy until yield point, respectively. Results: We analysed 299 patients, 163 patients with OP and 136 with severe OA. OA patients were more frequently men (67%, p < 0.001), significantly younger (67.5 ± 11.1y vs 78.9 ± 9.0y, p < 0.001) and fatter (body mass index (Kg/m 2 ) 28.1 ± 4.7 vs 23.92 ± 4.1, p < 0.001). OA patients fell less (number of falls in the last year 0.44 ± 0.49 vs 0.12 ± 0.32, p < 0.001). Only 15% of OP patients were being treated. Stiffness, strength and toughness were significantly increased in OA group (p = 0.005, 0.02 and 0.004, respectively), with adjustment to age and sex. Alkaline phosphatase was higher in OP patients (p = 0.05, with adjustment to age, sex and BMI), the other parameters didn't reach statistical difference. In OP patients, P1NP (coef = -1.42, p = 0.045) was associated with lower stiffness. In OA patients, P1NP (coef = -3.82, p = 0.006) and B-CTX (coef = -4.61, p = 0.035) were also associated with bone stiffness. P1NP was also associated with lower strength (coef = -0.058, p = 0.013). All analyses were adjusted to age, sex and BMI. Conclusions: In both OA and OP patients, P1NP was associated with lower stiffness. This tendency was also found with strength in OA patients. This may reflect that extreme values P1NP associate with bone fragility. This study was performed on a post-surgery context and further studies in other populations should be done.